The 'doublethink' of data: educational performativity and the field of schooling practices. Issue 5 (4th July 2017) - Hardy, Ian; Lewis, Steven
Abstract: This article provides insights into teachers' and school administrators' responses to the current 'fetishisation' of school performance data in Australian schooling. Specifically, the research investigates the accountability practices that emerged in a Queensland metropolitan primary school in response to this broader focus upon performance data. Drawing upon interviews with teachers and school administrators, literature and theorising on educational performativity and data, and Bourdieu's theory of practice, the article reveals how performative, data-driven practices play out at the level of the school. This process reveals a 'field of schooling practices' characterised by contradictory and contested logics of deifying, delivering and denying data. We describe this as the 'doublethink of data', involving teachers engaging with performative processes for purposes of compliance but without any real sense of the value of doing so. The research reveals the extraordinary energy involved in this work, and cautions against these performative practices and associated technologies.